2021
DOI: 10.36232/jurnalpendidikanbahasa.v8i2.1146
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students' Perspective on Self-Directed Learning in Speaking Skill

Abstract: This study aims to describe undergraduate students' perspectives on the implementation of self-directed learning in improving speaking skills. The participants of this research are 8th semester students at Universitas Singaperbangsa Karawang with the amount of 30 students. This study employed descriptive method, where the data gained through semi-structured interview and questionnaires. The findings indicated that all participants agreed that self-directed learning is an effective method that is used outside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In addition to the benefits of using Duolingo as a vocabulary learning assistant application, the researcher found that more students felt the benefits of Duolingo than those who did not. The results of this study are the same as that of (Miftakh & Yulianti, 2021) who stated that in their research on the perception and experience of secondary students in using Duolingo, they received positive responses from students where they felt facilitated to learn vocabulary using Duolingo. Where in the study both used interviews to obtain the data needed in the study and found that most of the respondents in the study stated that they felt the benefits after using Duolingo.…”
Section: Discussionsupporting
confidence: 77%
“…In addition to the benefits of using Duolingo as a vocabulary learning assistant application, the researcher found that more students felt the benefits of Duolingo than those who did not. The results of this study are the same as that of (Miftakh & Yulianti, 2021) who stated that in their research on the perception and experience of secondary students in using Duolingo, they received positive responses from students where they felt facilitated to learn vocabulary using Duolingo. Where in the study both used interviews to obtain the data needed in the study and found that most of the respondents in the study stated that they felt the benefits after using Duolingo.…”
Section: Discussionsupporting
confidence: 77%
“…The importance of SDL skills cannot be denied. According to Yulianti et al (2021), selfdirected students can use their knowledge and abilities in various contexts and continue to improve their learning capabilities throughout their lives. They further state that by giving students the freedom to learn what is essential from their perception, learning motivation is increased and the students are motivated to develop their SDL abilities.…”
Section: Strategies To Promote Sdl As Learning Presencementioning
confidence: 99%
“…It correlates with students in this modern era, where they can learn at their own pace by taking responsibility and actively participating in their learning process (Cakiroglu & Ozturk, 2021). In addition, Yulianti et al (2021) also argue that students need to take accountability for their learning because they cannot grasp the subject matter entirely through the teacher's explanations in class. Consequently, students are expected to evolve into self-regulated learners to broaden their comprehension of learning outside of the classroom, which may assist them in achieving tremendous academic success.…”
Section: Introductionmentioning
confidence: 99%